Exploring Teachers’ Pedagogical Experiences and Learning Practices in Araling Panlipunan 7: A Qualitative Inquiry at Divisoria High School - Blas, Dorothy Rose; Martin, Matt (Studies in Technology and Education, 2026)
The teaching of Araling Panlipunan plays a significant role in developing learners’ historical understanding, civic awareness, and cultural identity. However, effective pedagogy in Social Studies classrooms requires teachers to adopt diverse instructional strategies that respond to students’ learning needs and contextual realities. This qualitative study explored the pedagogical experiences of teachers and the learning practices implemented in Araling Panlipunan 7 at Divisoria High School. Using a qualitative inquiry design, data were gathered through semi-structured interviews, classroom observations, and document analysis involving Araling Panlipunan teachers. Thematic analysis was employed to identify recurring patterns and themes from the collected data. Findings revealed that teachers utilize contextualized instruction, collaborative learning strategies, and inquiry-based approaches to enhance student engagement and understanding of historical and socio-cultural concepts. Teachers also highlighted challenges related to limited instructional resources, time constraints, and varying student learning abilities. Despite these challenges, educators demonstrated adaptive pedagogical practices to foster meaningful learning experiences. The study concludes that reflective teaching practices, contextualized learning strategies, and continuous professional development are essential in improving Social Studies instruction. The findings provide valuable insights for curriculum planners, school administrators, and educators in strengthening pedagogical practices in Araling Panlipunan classrooms.